2023
DOI: 10.1111/dom.15157
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid lowering and effects of sodium‐glucose cotransporter‐2 inhibitors on gout: A meta‐analysis and meta‐regression of randomized controlled trials

Abstract: Aims To pool the effects of sodium‐glucose cotransporter‐2 (SGLT2) inhibitors on gout and to investigate the association of these effects with baseline serum uric acid (SUA), SUA lowering, and underlying conditions, such as type 2 diabetes mellitus (T2DM)/heart failure (HF). Methods PubMed, Embase, Web of Science, Cochrane Library and clinical trial registry websites were searched for randomized controlled trials (RCTs) or post hoc analyses (≥1‐year duration; PROSPERO:CRD42023418525). The primary outcome was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Regardless of its precise mechanism, it has been known for a while that SGLT-2 inhibitors could significantly reduce serum uric acid levels in patients with type 2 diabetes mellitus 6 . Recently, Banerjee M et al reported that SGLT2 inhibitors significantly reduced the risk of gout in individuals with type 2 diabetes mellitus and/or heart failure (HF) using data from five randomized controlled trials (RCTs) [71].…”
Section: Diabetes Mellitus (Glucose Metabolism)mentioning
confidence: 99%
“…Regardless of its precise mechanism, it has been known for a while that SGLT-2 inhibitors could significantly reduce serum uric acid levels in patients with type 2 diabetes mellitus 6 . Recently, Banerjee M et al reported that SGLT2 inhibitors significantly reduced the risk of gout in individuals with type 2 diabetes mellitus and/or heart failure (HF) using data from five randomized controlled trials (RCTs) [71].…”
Section: Diabetes Mellitus (Glucose Metabolism)mentioning
confidence: 99%
“…Recent meta‐analyses have demonstrated that, in general, SGLT2 inhibition reduces SUA levels in patients with type 2 diabetes by approximately 0.6 mg/dL as compared to placebo or control treatment 5,6 . Additionally, previous studies showed that the risk of gout and the need for the introduction of uric acid‐lowering therapy was reduced by SGLT2 inhibition in patients with diabetes and those with heart failure 7,8 . However, whether specific patient subgroups might achieve greater benefits in terms of reducing SUA levels with SGLT2 inhibition is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] This risk of GMI may deprive men of the cardio-renal-metabolic benefits of this group of drugs. [ 3 4 ] The notion that circumcision status may influence the risk of developing SGLT2i-associated GMI has not been prospectively evaluated to date. This study aimed to prospectively explore the impact of different baseline patient characteristics, i.e.…”
mentioning
confidence: 99%